Assessment of Some Physicochemical Parameters around Gold Mining Areas of Rimi, Sumaila Local Government Area, Kano State, Nigeria - Abubakar, Musa Yahaya; Dwanga, Mudwa Danladi; Adam, Ansar Bilyamin; Abubakar, Shitu Muhammad (Kwaghe International Journal of Sciences and Technology, 2024)
This study investigates the physicochemical parameters of ten hand-dug wells in Rimi Sumaila L.G.A. of Kano State. The parameters studied were pH, electrical conductivity, hardness, alkalinity, and turbidity. As a result of the studies, pH was between 7.18 and 8.55. The result shows that some areas, including Kofar Gabas, Kofar Kudu, Kofar Arewa, Company I, Company II, Company III, U.Kachaka, U.Dukawa, and U.Kuka, are alkaline in nature, while the pH in Kofar Yamma was 7.18, which is neutral. The electrical conductivity shows variation, such that the lowest value of conductivity was observed in Company III at 142 µS/cm, while the highest value was observed at Kofar Gabas at 708 µS/cm. The hardness was ranged between 173 and 370 mg/L. The highest values were observed at Kofar Gabas, and the lowest values were observed at Ukuka. The total hardness of water is the total soluble magnesium and calcium salts present in the water, expressed as CaCO3. The alkalinity analyzed ranged between 14 and 38 mg/L. The highest values were observed at U. Dukawa and the lowest values were observed at U. Kachaka, and the turbidity of the water analyzed ranged between 1 and 8.3 NTU. The highest values were observed at Company I, and the lowest values were observed at K. Arewa and U. Kuka.